Efecto de fertilizantes nitrogenados de liberación controlada en la producción de arroz (Oryza sativa L.) en la zona de Ricaurte, provincia de Los Ríos - Vera Vera, John Ernesto (2019)
VIII. SUMMARY The present experimental work was carried out in the farm "Don Viche" owned by Mr. Vicente Vera Lozano, it is located in the Precinct “La Casitas” at km 15 way Ricaurte-Ventanas. Eight treatments and three repetitions were investigated. The research aimed at the application of controlled release nitrogenous fertilizers in rice production. Rice sowing was carried out with the INIAP-15 and FL-01 varieties in experimental units of 16 m2. The treatments were distributed in a split plot design. The evaluation of means was made with the Tukey test at 5% significance. The variables evaluated were: height of plants, number of tillers per m2, grains per panicle, length and number of panicles m2, days to flowering, days to harvest, number of grains per panicle, weight of seed grain and yield per hectare. The results found in the present experimental work, shows that the application of fertilizers nitrogen controlled release, are an alternative in the nutritional system of rice cultivation, because they maximize grain production. The highest yield of the crop (6142,50 kg/ha) was presented by applying Multicote 350 kg/ha in the variety FL-01.